Mononuclear and Dinuclear Manganese(II) Complexes from the Use of Methyl(2-pyridyl)ketone Oxime - Constantinos G. Efthymiou; Vassilios Nastopoulos; Catherine Raptopoulou; Anastasios Tasiopoulos; Spyros P. Perlepes; Constantina Papatriantafyllopoulou (Bioinorganic Chemistry and Applications)
The reactions of methyl(2-pyridyl)ketone oxime, (py)C(Me)NOH, with manganese(II) sulfate monohydrate have been investigated. The reaction between equimolar quantities of MnSO4⋅H2O and (py)C(Me)NOH in H2O lead to the dinuclear complex [Mn2(SO4)2{(py)C(Me)NOH}4]⋅(py)C(Me)NOH, 1⋅(py)C(Me)NOH, while employment of NaOMe as base affords the compound [Mn(HCO2)2{(py)C(Me)NOH}2] (2). The structures of both compounds have been determined by single crystal X-ray diffraction. In both complexes, the organic ligand chelates through its nitrogen atoms. The IR data are discussed in terms of the nature of bonding and the structures of the two complexes.